2007
DOI: 10.1038/sj.cdd.4402141
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 in glutamate-dependent adult brain function and dysfunction

Abstract: Matrix metalloproteinase-9 (MMP-9) is extracellularly operating protease that is expressed by the adult brain neurons and released in response to enhanced neuronal activity driven by glutamate. In addition, MMP-9 can also be produced by glial and endothelial cells as well as by infiltrating leukocytes. Extracellularly, the protein is activated in a cascade of steps that involves also other proteases and then is inhibited by tissue inhibitors of matrix metalloproteinases (TIMPs). Under physiological conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…Hence, MMP-9 is the first YY1-dependent gene identified in the adult neurons. It codes for an enzyme engaged in the regulation of neuronal plasticity (52)(53)(54) and can also contribute to neuronal cell death in pathological conditions (55). Thus, our data suggest that YY1 can also be implicated in neuronal plasticity as well as in neurodegeneration.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, MMP-9 is the first YY1-dependent gene identified in the adult neurons. It codes for an enzyme engaged in the regulation of neuronal plasticity (52)(53)(54) and can also contribute to neuronal cell death in pathological conditions (55). Thus, our data suggest that YY1 can also be implicated in neuronal plasticity as well as in neurodegeneration.…”
Section: Discussionmentioning
confidence: 81%
“…MMPs are a large family of zinc dependent proteinases that are considered major elements conducting the extracellular matrix (ECM) remodeling and have pivotal role in cancer invasion and metastasis (1,34). Many studies have identified that MMPs are associated with various central nervous system (CNS) pathologies including stroke, traumatic brain injury, cerebral arteriovenous malformation, influenza associated encephalopathy and in bacterial meningitis where it has been identified as a risk factor for developing neurological sequel (8,22,39). Moreover, many studies have reported that MMP-9 has implication in synaptic plasticity, learning and memory (21,25,28,36).…”
Section: Acar G Et Al: Mmp-9 Expression In Temporal Lobe Epilepsymentioning
confidence: 99%
“…The extensive data indicate that MMP9 is a molecule of great importance for neuronal physiology and pathology. Its activation appears to be intimately linked to glutamate acting as a potent neurotoxin (37). Recent studies indicate that MMP9 is an important participant in aberrant plasticity and neuroinflammation and neuronal death and it is upregulated in experimental epilepsy models (38).…”
Section: Discussionmentioning
confidence: 99%